Solve ( D3 – 3DD′2+2D′3 )Z = e2x – y
"( D^3 \u2013 3DD'^2+2D'^3)Z = e^{2x \u2013 y}"
Replace D with m and D' with 1
Auxiliary equation becomes "m^3-3m+2=0"
"(m-1)(m^2+m-2)=0"
(m-1)(m-1)(m+2)=0
m=1,1,-2
"C.F=f_1(y+x)+xf_2(y+x)+f_3(y-2x)"
For particular integral;
"P.I=\\frac{1}{( D^3 \u2013 3DD'^2+2D'^3)} e^{2x \u2013 y}"
Put D=2 and D'=-1
"P.I=\\frac{1}{( 2^3 \u2013 3(2)(-1)^2+2(-1)^3)} e^{2x \u2013 y}"
"=\\frac{1}{8-6-2)}e^{2x-y}"
We then differentiate the denominator w.r.t D and multiply by x to get,
"P.I=\\frac{x}{\\frac{d}{dD}( D^3 \u2013 3DD'^2+2D'^3)} e^{2x \u2013 y}"
"=\\frac{x}{( 3D^2 \u2013 3D'^2+0)} e^{2x \u2013 y}"
"=x\\frac{1}{( 3D^2 \u2013 3D'^2)} e^{2x \u2013 y}"
Now put D=2 and D'=-1
"=x\\frac{1}{( 3(2)^2 \u2013 3(-1)^2)} e^{2x \u2013 y}\\newline=x\\frac{1}{( 12\u2013 3)} e^{2x \u2013 y}"
"P.I=\\frac{x}{9}e^{2x-y}"
The solution to the equation becomes,
z=C.F+P.I
"=f_1(y+x)+xf_2(y+x)+f_3(y-2x)+\\frac{1}{9}xe^{2x-y}"
Comments
Leave a comment